(untitled) (Revista Crioula, 2023)
This article presents, aligned with Freire's (1967; 1996; 2020) and Bakhtin's (2002; 2010) concepts of dialogy, and Cosson's (2006) literary literacy, in a cultural-historical approach, the practices of teaching literature from the perspective of a poetic education. From participant observation, dialogical experiences were developed in a high school on the outskirts of Manaus-Amazonas. The results showed that an active literary education contributes to the development of critical perception, which enables the expression of subjectivity.